Conceptualizing social dynamic capabilities: Contextual embeddedness in hospitality industry - Dias, Á.; Zizka, L.; Bernard, S.; Singal, M.; Ho, J. A. (International Journal of Hospitality Management, 2026)
This study introduces the concept of Social Dynamic Capabilities to address the growing need for hospitality organizations to align business strategies with social sustainability goals. Employing a grounded theory approach, we develop propositions and a conceptual framework delineating social dynamic capabilities from the broader concept of dynamic capabilities. Our research was conducted in two phases: an exploratory phase to identify core skills and practices for social dynamic capabilities and a confirmatory phase to refine the framework. The findings underscore the importance of stakeholder collaboration and community involvement in the operationalization of social dynamic capabilities, leading to the concept of Collaborative Social Transformation. Our study advances the dynamic capabilities framework by extending it into the social domain and providing a practical framework for implementation. This study provides a new perspective on integrating social sustainability issues into long-term organizational practices.